Perceptions and Experiences of Women’s Captivity in the Sixteenth-Century Spanish Army - Suárez García, Sandra (Cuadernos de Historia Moderna, 2025)
This article revolves around two key questions: first, how 16th-century Spanish military men perceived and experienced the capture of women and young girls in the European and Mediterranean context. Second, how we can recover the voices of these female captives and reconstruct their particular experiences. To address these issues, the study employs a qualitative analysis of sixteenth-century military literature—including war chronicles, (auto)biographies, and treatises—as well as archival documentation, particularly from the Kingdom of Granada. It shows a multifaceted understanding and lived experience of the phenomenon, encompassing multiple perceptions and experiences of female captivity, ranging from individual economic benefit to the loss of a loved one. Furthermore, it underscores the potential of military documentary sources for retracing the first moments of women’s experiences of captivity.